Sustainability and the Rights of Nature in Practice - La Follette, Cameron; Maser, Chris (Taylor & Francis, 2019)
This book, and the intellectual and legal movement summarised within its pages, charts a bold alternative course for humanity. That there are certain 'rights of Nature' intrinsic to landscapes and life-forms around the world is a revolutionary assertion, yet an assertion with abundant and venerable precedents. By the logic of this movement, nonhuman beings have intrinsic existential rights and, by extension, should possess certain rights protecting their survival and interests within the evolving legal practices of modern nations. Concepts akin to human rights are thus extended to populations of wild nonhuman species, and to landforms such as mountains or rivers, on which many other lives depend. These entities might then possess rights to representation in legal arenas akin to personhood - so that certain keystone landforms or living beings cannot be destroyed for the profit of human individuals without overwhelmingly compelling reasons, nor damaged without efforts to directly compensate nonhuman 'claimants' for damages.